2007
DOI: 10.1007/s11695-008-9423-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Related to Nonalcoholic Steatohepatitis in Severely Obese Subjects

Abstract: MetS and NASH were common in severely obese Taiwanese adults. Presence of MetS, high blood pressure, and high fasting glucose was independently related to increased risk of NASH. The underlying mechanism deserves to be explored in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…The hypertransaminasemia in NASH was found to be SGPT dominant in our study. Similar findings were reported by Sugimoto et al (2003) (17) . Singh et al,(2010)in their comparative study between NASH and ASH clearly showed SGPT levels were more elevated in NASH as compared to ASH(mean being110.82IU/L in NASH and 79.69IU/L in case of ASH).Also showed a higher AST/ALT ratio in ASH as compared to NASH(mean of 1.24+0.81 in ASH and 0.68+0.33 in NASH)This study strongly supports our finding that SGPT is a more relevant marker than SGOT in NASH patients and AST/ALT ratio Is >1 in ASH rather than NASH, which indeed helps in distinguishing between ASH and NASH.…”
Section: Discussionsupporting
confidence: 92%
“…The hypertransaminasemia in NASH was found to be SGPT dominant in our study. Similar findings were reported by Sugimoto et al (2003) (17) . Singh et al,(2010)in their comparative study between NASH and ASH clearly showed SGPT levels were more elevated in NASH as compared to ASH(mean being110.82IU/L in NASH and 79.69IU/L in case of ASH).Also showed a higher AST/ALT ratio in ASH as compared to NASH(mean of 1.24+0.81 in ASH and 0.68+0.33 in NASH)This study strongly supports our finding that SGPT is a more relevant marker than SGOT in NASH patients and AST/ALT ratio Is >1 in ASH rather than NASH, which indeed helps in distinguishing between ASH and NASH.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, NAFLD is the most prevalent liver disease in the United States, representing 20 to 30% of all liver disease cases (Bedogni et al, 2005). With obesity and obesity-related conditions (insulin resistance, dyslipidemia, and high blood pressure) identified as predisposing conditions, the occurrence of NAFLD is increasing as well (Huang et al, 2007;Targher et al, 2008). NAFLD composes a spectrum of etiologies ranging from simple fatty liver (steatosis) to the more severe nonalcoholic steatohepatitis (NASH).…”
mentioning
confidence: 99%
“…In this study, hypertension, hypercholesterolemia, hypertriglyceridemia, lower HDL, and higher fasting plasma glucose, the components of metabolic syndrome, are significantly related to NAFLD. Metabolic syndrome could be viewed as a strong predictor of NAFLD and NAFLD is also a good predictor for the clustering of components of risk factors for metabolic syndrome [25,26]. In addition, clinical manifestation of NAFLD is usually absent or subtle with abnormal aminotransferase or incidental radiographic findings of fatty liver [27].…”
Section: Discussion Prevalence and Cardiovascular Factors For The Devmentioning
confidence: 99%